Will a government find it financially easier to neutralize a looming protest if more groups are involved? - Oded Stark; Ewa Zawojska (University of Bonn, Center for Development Research (ZEF), 2016)
We study a policy response to an increase in post-merger social stress. If a merger of groups of people is viewed as a revision of their social space, then the merger alters people's comparators and increases social stress: the social stress of a merged population is greater than the sum of the levels of social stress of the constituent populations when apart. We use social stress as a proxy measure for looming social protest. As a response to the post-merger increase in social stress, we consider a policy aimed at reversing the negative effect of the merger by bringing the social stress of the merged population back to the sum of the pre-merger levels of social stress of the constituent populations when apart. We present, in the form of an algorithm, a cost-effective policy response which is publicly financed and does not reduce the incomes of the members of the merged population. We then compare the financial cost of implementing such a policy when the merger involves more or fewer groups. We show that the cost may fall as the number of merging groups rises.
Keywords: D04; D63; F55; H53; P51; 330; merger of populations; revision of social space; aggregate relative deprivation; social stress; a cost-effective policy response